Conformational Structures of a Decapeptide Validated by First Principles Calculations and Cold Ion Spectroscopy. Issue 7 (26th February 2015) - Roy, Tapta Kanchan; Kopysov, Vladimir; Nagornova, Natalia S.; Rizzo, Thomas R.; Boyarkin, Oleg V.; Gerber, R. Benny
Abstract Calculated structures of the two most stable conformers of a protonated decapeptide gramicidin S in the gas phase have been validated by comparing the vibrational spectra, calculated from first‐ principles and measured in a wide spectral range using infrared (IR)–UV double resonance cold ion spectroscopy. All the 522 vibrational modes of each conformer were calculated quantum mechanically and compared with the experiment without any recourse to an empirical scaling. The study demonstrates that first‐principles calculations, when accounting for vibrational anharmonicity, can reproduce high‐resolution experimental spectra well enough for validating structures of molecules as large as of 200 atoms. The validated accurate structures of the peptide may serve as templates for in silico drug design and absolute calibration of ion mobility measurements.